Estrategia diagnóstica de paratuberculosis en bovinos - Gilardoni, Liliana Rosa (2012)
Paratuberculosis (PTB) is a chronic disease of ruminants, characterized by a long incubation period and development of granulomatous enteritis and diarrhea in advanced stages of the disease. It is caused by Mycobacterium avium\nsubspecies paratuberculosis (Map). Its economic relevance is due to reduced\nmilk yield, progressive cachexia and mortality.\nDepending on the severity of clinical signs, the evolution of bovine PTB can be\ndivided into four stages: silent, subclinical, clinical, and advanced. The animals\nin the early stages, which are usually the longest, excrete Map by colostrum,\nmilk and feces, with no evidence of clinical signs. In this way, the spread of the\ninfection to other susceptible animals, particularly calves, takes place. For these reasons, control of the disease should be based on early detection\nand rapid culling of infected animals. However, currently available diagnostic\ntests have not enough sensitivity to do feasible the implementation of this type\nof strategy. The recognized and currently in use diagnostic tests for the diagnosis of PTB\nare fecal culture and indirect ELISA test for the detection of serum antibodies. In\nsubclinical stages the sensitivity of these tests is below 50%. In order to improve the diagnostic sensitivity, biotechnology was applied for the\ndevelopment of new methods, as the polymerase chain reaction (PCR) that can be applied in feces, milk and tissues samples.\nHowever, the elimination of Map by feces or milk is intermittent and with a low\nconcentration. Therefore to increase sensitivity a method of concentration of\nMap was developed: immunomagnetic separation (IMS) using magnetic\nnanoparticles coupled to polyclonal antibodies antiMap. The procedure applied to bovine milk not only increases the concentration of Map, but also removes\nthe milk components PCR inhibitors. The purpose of this thesis was to develop a procedure to identify Map in milk samples. The developed protocol has two stages: a. concentration of microorganisms by immunomagnetic separation with magnetic nanoparticles (immunomagnetic beads) coupled to specific\nmonoclonal and polyclonal antibodies produced in the Faculty of Veterinary Science, University of Buenos Aires.\nb. identification of genetic material by the application of IS900 PCR with\nprimers designed in the same Faculty.\nIn addition, in order to evaluate the performance of the method in field\nconditions (preliminary assessment), samples from dairy cows from both\ninfected and free farms were analyzed. The maximum adhesion of immunomagnetic beads was obtained when beads\ncoupled to monoclonal antibodies were used simultaneously with beads\ncoupled to polyclonal antibodies (107 CFU/mL).\nA greater analytical sensitivity was obtained with the IS900 PCR with primers\ndesigned by Dr. S. L, Mundo, at the Faculty of Veterinary Science, compared to\nthe IS900 PCR with primers designed by Dr. Collins et al. and ISF57 PCR (the\nmethods were able to detect 101, 103 and 102 Map CFU/mL respectively).\nFurthermore, the IS900 PCR did not present cross-reaction when they were\ntested with other mycobacteria like M. avium subsp. avium, M. phlei, M.\nfortuitum and M. scrofulaceum.\nIn field conditions, was used the milk, feces and blood samples of 147\nasymptomatic dairy cows from 5 infected farms and 118 of cows with same\ncondition from 4 free-farms. These samples were analyzed by the method\ndeveloped (IMS-PCR IS900), by milk and fecal culture MF and by indirect\nELISA in serum.\nFrom the infected farms samples were obtained following positive results: IMSIS900 PCR: 80 (54.4%), milk culture: 2 (1.4%), fecal culture: 17 (11.6 %) and\nELISA: 52 (35.4%). The 118 samples from the 4 free-farms were negative to all\ntests. The agreement between IMS-IS900 PCR and fecal culture and between IMSIS900\nPCR and ELISA showed a low level. This is consistent with the low sensitivity that those methods present in the asymptomatic cows. The sensitivity and specificity for the fecal culture with respect to IMS-IS900 PCR were\nestimated at 18.8% and 98.9% respectively. For ELISA, these parameters were estimated at 36.2% and 87.6% respectively.\nThe absence of positive results in the free farms is an indicator of the high level\nof specificity shown by the IMS-IS900 PCR.\nThe results obtained in this work suggest that IMS-IS900 PCR technique has a\ndiscriminatory capacity more efficiently than currently available tests.\nFurthermore, this technique in comparison with the fecal or milk culture has the\nadvantage in processing time, which is significantly lower than that required for\nculture. The above justifies the method is validated and subsequently deployed for use as routine diagnosis of field samples.